A review on graphene quantum dots and their nanocomposites: from laboratory synthesis towards agricultural and environmental applications - Facure, Murilo H. M; Schneider, Rodrigo; Mercante, Luiza A; Correa, Daniel S (Environmental science. Nano, 2020)
Graphene quantum dots (GQDs) are 0D materials belonging to the carbon-based family that present some interesting characteristics of graphene combined with a tunable bandgap emerging from their reduced size, which gives them final outstanding physical-chemical properties. Furthermore, GQDs can be combined with other materials to produce nanocomposites with remarkable properties and superior performance. In this review, we present a timely survey on how the structural characteristics and physical-chemical properties of GQDs enable their use in advanced composite materials for agricultural and environmental applications. Specifically, emphasis is given to GQD-based composites in the form of films, nanofibers, aerogels, and molecularly imprinted polymers. The unique properties of GQD nanocomposites are suitable for designing devices employed in: i) filtration membranes and adsorbent materials for contaminant removal; ii) optical devices and (bio)sensors with different transduction modes for detecting hazardous analytes including pesticides, heavy metals, antibiotics, and food contaminants; iii) and novel catalyst systems for degrading pollutants. Finally, current challenges and future prospects on industrial applications of GQD-based composites are also discussed. This review highlights recent and important advances related to the synthesis, characterization and application of graphene quantum dot (GQD)-based nanocomposites for the agriculture and environmental sectors.